(untitled) (Journal of Parents and Teachers, 2013)
This article presents possible activities to work autonomy and personal initiative skill from two Disney songs: “You’ve got a friend in me” and “This is me”. They are ideas that the teacher should adapt to his/her classroom context. It deals with topics like self-esteem, friendship or responsibility and it combines team work and individual work.